Nonlinear analysis of slender hollow steel sections based on the global deformations analysis - Baptista, A. M. (1995)
This paper presents a geometric and material nonlinear model of analysis for the study of rectangular thin-walled steel box compressed members. The local buckling of the section's walls is taken in account by simplified piecewise linear stress-strain curves, based on extensive studies of several authors. The cross section's efforts and stiffness terms are calculated by analytical expressions, based on the analysis of the cross section's global deformations, which enable a very fast study of the behaviour of these structural members. The performance of this model is illustrated by the comparison of its results with those published by other authors, obtained by numerical and experimental studies.